Pengaruh Promosi dan Harga terhadap Minat Beli Mahasiswa Fakultas Ekonomi Universitas Pendidikan Ganesha pada Aplikasi Tiktokshop - Yanti, Ni Luh Putu Erna; Sujana, I Nyoman (Universitas Pendidikan Ganesha, 2025)
The aim of this study is to examine: (1) the effect of promotion on the purchase intention of students in the Faculty of Economics using the TikTok Shop application, (2) the effect of price on the purchase intention of students in the Faculty of Economics using the TikTok Shop application, and (3) the simultaneous effect of promotion and price on the purchase intention of students in the Faculty of Economics using the TikTok Shop application. This study employs a quantitative research method with a causal approach. The population of this study consists of active students from the Faculty of Economics, class of 2021. The sample used in this research comprises 116 students from the total active students of the Faculty of Economics, Universitas Pendidikan Ganesha, class of 2021. The data analysis technique applied in this study is multiple linear regression analysis, with hypothesis testing conducted using partial tests (t-tests) and classical assumption tests. The results of this study indicate that: (1) promotion has a positive and significant partial effect on students' purchase intention, (2) price has a positive and significant partial effect on students' purchase intention, and (3) promotion and price simultaneously have a positive and significant effect on students' purchase intention.